Testament of a liberal - Patel, Dorab (Karachi : Oxford University Press, 2000)
Historical study chiefly on law-making in Pakistan; from the promulgation of the first Constitution in 1947 to the present times.
Includes index.
Keywords: Constitutional history -- Pakistan; Pakistan -- Politics and government